A concepção de homem em Marx: uma análise dos Manuscritos econômico-filosóficos de 1844. - Sandeski, Margarida Maria (2016)
This dissertation has an objective to show the concept of man in Marx from the Economic-Philosophic Manuscript of 1844. For justification of this purpose, relevant categories will be discussed such as: work, private property, alienation, estrangement, destrangement and emancipation. We seek to understand: 1) how man, between alienated and estranged work, can achieve the quality of emancipated man; 2) how a Marx theoretical construction contributes by work proposition as founding category of social being, for man builds and rebuilds himself in the midst a capitalist society. First, we are going to show that the founding structure of the capitalist system is in a private property. The capitalist, when uses the estranged work, empowers the capital gain, makes the social division of work an instrument of worker accumulation and exploitation which earns a too little pay and his existence just has sense while it is useful to the capitalist, i.e. he does not exist as a human, but only as human good. To maximize the gains of capital, the capitalist structure feeds itself by man work which turned into good is sold by a wage which guarantees his survival. In this way, work and capital depend each other, the worker aims in the work, his existence is subjected in object and the human dimension is emptied. Second, we start with the assumption of the capitalist society has in the private property a production way which uses the alienated work to get and enhance its capital. Thus, the man by the modern conditions is in an alienation condition and generates the estrangement of the man in relation to his work product, in his activity, in his generic being in relation to the other men. The loss of himself, in his activity performance (work) changes his life in mere way of life and the man while he becomes alienated and estranged, his exteriority opposes him because it takes part of a set of social coercions; So Marx points out in the private property the cause of this man estrangement. Finally, we are going to talk at length about the man, the only being who can register in his own nature the freedom attribute as a becoming. Marx shows us that by a practical and real action, to remove the estrangement by the destrangement and build emancipatory actions. By the revolutionary action, the private property and the estranged work, which result in man brutalization, form this way besides the reflection about awareness importance of the working class which can support his estrangement state understanding the world is produced by it, since the capitalism is a historic construction. So, the man when requires his emancipation, which does not occur without a deep social transformation, notices this revolutionary action is not the return of his state of nature, but for the emancipation is connected to the history and aims the development of human capacities.